Gemfibrozil, a Lipid-lowering Drug, Inhibits the Induction of Nitric-oxide Synthase in Human Astrocytes - Pahan, Kalipada (2002)
Gemfibrozil, a lipid-lowering drug, inhibited cytokine-induced production of NO and the expression of inducible nitric-oxide synthase (iNOS) in human U373MG astroglial cells and primary astrocytes. Similar to gemfibrozil, clofibrate, another fibrate drug, also inhibited the expression of iNOS. Inhibition of human iNOS promoter-driven luciferase activity by gemfibrozil in cytokine-stimulated U373MG astroglial cells suggests that this compound inhibits the transcription of iNOS. Since gemfibrozil is known to activate peroxisome proliferator-activated receptor-α (PPAR-α), we investigated the role of PPAR-α in gemfibrozil-mediated inhibition of iNOS. Gemfibrozil induced peroxisome proliferator-responsive element (PPRE)-dependent luciferase activity, which was inhibited by the expression of ΔhPPAR-α, the dominant-negative mutant of human PPAR-α. However, ΔhPPAR-α was unable to abrogate gemfibrozil-mediated inhibition of iNOS suggesting that gemfibrozil inhibits iNOS independent of PPAR-α. The human iNOS promoter contains consensus sequences for the binding of transcription factors, including interferon-γ (IFN-γ) regulatory factor-1 (IRF-1) binding to interferon-stimulated responsive element (ISRE), signal transducer and activator of transcription (STAT) binding to γ-activation site (GAS), nuclear factor-κB (NF-κB), activator protein-1 (AP-1), and CCAAT/enhancer-binding protein β (C/EBPβ); therefore, we investigated the effect of gemfibrozil on the activation of these transcription factors. The combination of interleukin (IL)-1β and IFN-γ induced the activation of NF-κB, AP-1, C/EBPβ, and GAS but not that of ISRE, suggesting that IRF-1 may not be involved in cytokine-induced expression of iNOS in human astrocytes. Interestingly, gemfibrozil strongly inhibited the activation of NF-κB, AP-1, and C/EBPβ but not that of GAS in cytokine-stimulated astroglial cells. These results suggest that gemfibrozil inhibits the induction of iNOS probably by inhibiting the activation of NF-κB, AP-1, and C/EBPβ and that gemfibrozil, a prescribed drug for humans, may further find its therapeutic use in neuroinflammatory diseases.